Analisis Keuntungan Pedagang Ikan Segar Pasar Kalindo Kota Banjarmasin - Nurmadina, Alya; Fahrati, Eny (PPJP ULM, 2023)
This study aims to analyze the factors affecting fish traders' profits in the Kalindo Banjarmasin market. The research location is in the Kalindo Market Banjarmasin, with a population and sample of 31 traders. They are using quantitative descriptive analysis techniques. The data in this study were sourced from primary data from interviews and questionnaires. Variables consist of profit, working capital, working hours, labor, and types of merchandise. This study uses multiple linear regression analysis (OLS) with a significance level 0.05. The results of the study indicate that the factors of working capital, working hours, labor, and the type of merchandise together significantly affect the profits of Kalindo fish traders. Factors of operating money, working hours, and labor partially affect traders' profits. The influence of working capital factors, working hours, labor, and types of merchandise on fish traders' profit is 70%, and other factors explain 30%.